2018
DOI: 10.1186/s41935-018-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Medico legal procedures related to sexual assault: a 10-year retrospective experience of a Daphne protocol application

Abstract: Background: Sexual assault is a worldwide problem that has not yet been sufficiently acknowledged as confirmed by the literature. Italian law n.96, 1996, foreseeing norms regarding rape and sexual abuse, finally gave significant relevance to sex crimes. Results: Among victims 88 were females (97%) and 2 males (3%); 68 Italians (75.5%) and 22 foreigners (24.5%). At the time the events occurred, 42% (n = 38) of the victims were minors aged less than 16 years. In 11 cases, the age of the victim is not indicated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
(30 reference statements)
1
11
1
3
Order By: Relevance
“…This study also showed a significant association between bodily injuries in children and adults. The two most common types of injuries found in this study were similar to those found in a study in Spain, namely, bruises and abrasions, with the extremities being the most common site of injury (Moreno, 2013;Zerbo et al, 2018). More child victims had ano-genital injuries compared with adult victims.…”
Section: Sexual Violencesupporting
confidence: 87%
See 1 more Smart Citation
“…This study also showed a significant association between bodily injuries in children and adults. The two most common types of injuries found in this study were similar to those found in a study in Spain, namely, bruises and abrasions, with the extremities being the most common site of injury (Moreno, 2013;Zerbo et al, 2018). More child victims had ano-genital injuries compared with adult victims.…”
Section: Sexual Violencesupporting
confidence: 87%
“…Our study reported that 22.4% of sexual violence victims had bodily injury. The results were lower than those of previous studies reporting rates of 30.6% in Spain (Moreno, 2013), 41.8% in Taipei (Hwa et al, 2010) and 42% in Italy (Zerbo et al, 2018). Nevertheless, all of these studies reported similar patterns to those in our study, namely, the incidence of physical injury increased as the victim age increased (Hwa et al, 2010;Moreno, 2013).…”
Section: Sexual Violencecontrasting
confidence: 78%
“…Drug-facilitated crimes (DFCs) have globally increased and are currently a socio-medical emergency worldwide (Zerbo et al 2018). Drug-facilitated crimes are defined as crimes such as robbery, sexual assault, money extortion or battery when committed while the victim is under the influence of drugs (Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such program should include divesting the framework for receiving complaints of domestic violence from the Police authorities whose operational procedure in Nigeria can be quite harrowing for both victim and assailant. In addition, introduction of a standardized protocol could streamline and improve evidence gathering as well as health management of victims of sexual violence (Zerbo 2018).…”
Section: Discussionmentioning
confidence: 99%